Studi Eksegesis 2 Korintus 11:4 Mengenai “Yesus yang Lain” dan Implikasinya terhadap Pembinaan Iman Jemaat - Prianto, Robi; Rusliadi, Rusliadi; Tampubolon, Yohanes Hasiholan (Sekolah Tinggi Teologi Sumatera Utara, 2023)
Another Jesus was a false doctrine taught by the false apostles to the Corinthians to lead astray the Lord’s congregation in Corinth. The teachings of the false apostles concerning another Jesus are those that are easy to understand and reasonable. When they believe in “another Jesus,